The Influence of Job Insecurity and Job Stress on Quitting Intentions, with Early Retirement as a Moderating Variable - Asdilvira, Beby; Ginting, Paham; Siahaan, Elisabeth (International Journal of Science, Technology & Management, 2023)
Intention to cease working is a condition that causes workers to willingly or involuntarily quit their occupations. Job instability is one of the variables that contribute to the desire to cease working. Additionally, job stress is a factor that contributes to the desire to cease working. The goal of this research was to examine the relationship between job instability and work stress and the desire to retire early. This study's demographic and sample consisted of 58 Xyz Aviation Medan Branch workers. Using descriptive analysis and moderated regression analysis, the data were evaluated (MRA). The findings revealed that job uncertainty and work stress had a positive and statistically significant influence on the desire to cease working. In addition, early retirement might amplify the impact of job uncertainty and stress on the decision to cease working.